(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
For the large sparse complex symmetric linear systems, by applying the minimal residual technique to accelerate a preconditioned variant of new Hermitian and skew-Hermitian splitting (P^∗NHSS) method and efficient parameterized P^∗NHSS (PPNHSS) method, we construct the minimal residual P^∗NHSS (MRP^∗NHSS) method and the minimal residual PPNHSS (MRPPNHSS) method. The convergence properties of the two iteration methods are studied. Theoretical analyses imply that the MRP^∗NHSS method and the MRPPNHSS method converge unconditionally to the unique solution. In addition, we also give the inexact versions of MRP^∗NHSS method and MRPPNHSS method and their convergence proofs. Finally, numerical experiments show the high efficiency and robustness of our methods.